Child Temperament and Home-Based Parent Involvement at Kindergarten Entry: Evidence From a Low-Income, Urban Sample. Issue 5 (4th July 2017) - Han, Jinjoo; O'Connor, Erin E.; McCormick, Meghan P.; McClowry, Sandee G.
ABSTRACT: Research Findings : Home-based involvement—defined as the actions parents take to promote children's learning outside of school—is often the most efficient way for low-income parents to be involved with their children's education. However, there is limited research examining the factors predicting home-based involvement at kindergarten entry for low-income families. This is a notable oversight given established links between parent involvement and children's educational outcomes. To learn more about this gap, we used data from 220 low-income, urban students to examine associations between 4 dimensions of child temperament—negative reactivity, task persistence, withdrawal/shyness, and motor activity—and home-based parent involvement. Parent–child conflict was also examined as a mechanism explaining associations between dimensions of child temperament and parent involvement. Hierarchical multiple regression analyses revealed that a withdrawn/shy temperament in children predicted lower levels of home-based parent involvement, whereas a task-persistent temperament predicted higher levels of home-based parent involvement. Parent–child conflict partially mediated the relationship between task persistence and home-based parent involvement. Practice or Policy : Results expand understanding of home-based involvement at kindergarten entry in low-income families and illuminate the need to consider child temperament within the context of early intervention programs.